Intracranial Fusiform and Circumferential Aneurysms of the Main Trunk: Therapeutic Dilemmas and Prospects - Guo, Yunbao; Song, Ying; Hou, Kun; Yu, Jinlu (Frontiers in Neurology, 2021)
Intracranial fusiform and circumferential aneurysms (IFCAs), especially those located on the main trunk, are uncommon and difficult to manage. Currently, literature focused on IFCAs on the main trunk of cerebral arteries is lacking. The treatment of IFCAs is still under debate. Therefore, in this review, we further explore the treatment of this complicated entity. In addition, we also present some interesting cases. Based on the literature review and our experience, we found that IFCAs are often located in the vertebrobasilar system and that ruptured or large symptomatic IFCAs are associated with increased mortality and higher rebleeding rates. The treatment strategies for IFCAs can be classified as deconstructive and reconstructive methods via open surgery and/or endovascular treatment (EVT). Currently, EVT is a popular method and the main therapeutic choice. In particular, flow diversion has revolutionized the treatment of IFCAs. Parent artery occlusion (PAO) with or without revascularization may still be considered a suitable choice. Complex IFCAs that cannot be resolved by EVT can also be treated via open surgery with or without extracranial–intracranial bypass. Targeted embolization for the weak points of IFCAs is a temporary or palliative choice that is rarely used. In summary, despite complications, both surgical treatment and EVT are effective options for appropriately selected cases. Due to the development of endovascular implants, EVT will have better prospects in the future.